PERSEPSI MAHASISWA TERHADAP ONLINE PEER FEEDBACK PADA TUGAS MENULIS DISCUSSION TEXT - Inayatul Ulya (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2023)
Writing is a productive activity where the writer expresses his/her ideas in the form of sentences, paragraphs or text. To know how far students’ writing skill mastered, it was needed to do feedback, one of them was online peer feedback. This study aimed to find out students’ perception on the implementation of online peer feedback on the project of writing discussion text. Mix method research was applied. The subject of the study were the 2nd semester students of English Education Department of Pekalongan University. Questionnaire, interview, and documentation were conducted to get the data. For the quantitative data, they were analyzed statistically. Meanwhile, for the qualitative data, they were described by doing data interpretation. The finding showed that students’ perceptions in terms of online peer feedback were that online peer feedback can be done flexibly and easily accessed. Through peer feedback, students can identify the colleagues writing, in terms of content, structure, linguistic features, vocabulary, and mechanics. Meanwhile, the obstacles faced were that it was not easy for students to compose words in delivering feedback. Keywords: Perception, online peer feedback, discussion text